Fritz Lang : The Nature of the Beast - McGilligan, Patrick (Book collections on Project MUSE., 2013)
The author spent four years in Europe and America interviewing Fritz Lang's dying contemporaries, researching government and film archives, and investigating the intriguing life story of the visionary director. Ultimately, this biography reconstructs the compelling, flawed human being behind the monster with the monocle.